Reduced internalization of TNF-ɑ/TNFR1 down-regulates caspase dependent phagocytosis induced cell death (PICD) in neonatal monocytes. - Stephan Dreschers; Christian Gille; Martin Haas; Florence Seubert; Christopher Platen; Thorsten W Orlikowsky (PLoS ONE)
Phagocytosis-induced cell death (PICD) is diminished in cord blood monocytes (CBMO) as compared to cells from adults (PBMO) due to differences in the CD95-pathway. This may support a prolonged pro-inflammatory response with sequels of sustained inflammation as seen in neonatal sepsis. Here we hypothesized that TNF-α mediated induction of apoptosis is impaired in CBMO due to differences in the TNFR1-dependent internalization. Monocytes were infected with Escherichia coli-GFP (E. coli-GFP). Monocyte phenotype, phagocytic activity, induction of apoptosis, and TNF-α/TNF-receptor (TNFR) -expression were analysed. In the course of infection TNF-α-secretion of CBMO was reduced to 40% as compared to PBMO (p<0.05). Neutralization of TNF-α by an αTNF-α antibody reduced apoptotic PICD in PBMO four-fold (p < 0.05 vs. infection with E. coli). PICD in CBMO was reduced 5-fold compared to PBMO and showed less responsiveness to αTNF-α antibody. CBMO expressed less pro-apoptotic TNFR1, which, after administration of TNF-α or infection with E. coli was internalized to a lesser extent. With similar phagocytic capacity, reduced TNFR1 internalization in CBMO was accompanied by lower activation of caspase-8 (p < 0.05 vs. PBMO). Stronger caspase-8 activation in PBMO caused more activation of effector caspase-3 and apoptosis (all p < 0.05 vs. PBMO). Our results demonstrate that TNFR1 internalization is critical in mediating PICD in monocytes after infection with E.coli and is reduced in CBMO.